2017
DOI: 10.1159/000479546
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 Mutation Is an Independent Inferior Prognostic Indicator for Patients with Myelodysplastic Syndromes

Abstract: Background: Genomic sequencing technologies have identified isocitrate dehydrogenase (IDH) mutations in haematological malignancies. The prognostic implications of somatic IDH mutation (mIDH) in myelodysplastic syndromes (MDS) remain controversial. Methods: Mutations in IDH1 and IDH2 were detected using genomic sequencing technologies in 97 patients with MDS. Results: Seven (7.2%) mutations were identified: 3 in IDH1 (all R132C) and 4 in IDH2 (3 R140Q and 1 R140L). The frequency of mutation was 16.6% (2/12) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In multivariate analysis, IDH1 mutations but not IDH2 mutations were associated with shortened leukemia-free survival [ 22 ]. Wang et al confirmed these findings in a group of 97 MDSs showing that patients with IDH1 mutations displayed shorter overall and progression-free survival, whereas IDH2 mutations did not have impact on OS and PFS [ 23 ].…”
Section: Idh Mutations In Myelodysplastic Syndromesmentioning
confidence: 82%
“…In multivariate analysis, IDH1 mutations but not IDH2 mutations were associated with shortened leukemia-free survival [ 22 ]. Wang et al confirmed these findings in a group of 97 MDSs showing that patients with IDH1 mutations displayed shorter overall and progression-free survival, whereas IDH2 mutations did not have impact on OS and PFS [ 23 ].…”
Section: Idh Mutations In Myelodysplastic Syndromesmentioning
confidence: 82%
“…DNMT3A mutations are more frequent in patients with AML (about 20%), whereas they are less common in patients with MDS (10%) . IDH1/2 (isocitrate deshydrogenase 1/2) mutations are closely associated with higher bone marrow blasts, lower neutrophil counts, and unspecific karyotypes . Mutant IDH1/2 can block myeloid differentiation and increase the accumulation of DNA damage in hematopoietic stem cell/myeloid progenitors leading to oncogenic transformation .…”
Section: Epigeneticsmentioning
confidence: 99%
“…IDH1/2 mutations vary from 4% to 12% in patients with MDS and are more common in AML . Furthermore, IDH1 mutations are an independent prognostic factor for patients with MDS . ASXL1 (addition of sex Combs‐like 1) and EZH2 (enhancer of zeste homolog 2) code for histone modifying enzymes and loss‐of‐function mutations are associated with poor survival in MDS.…”
Section: Epigeneticsmentioning
confidence: 99%
“…2HG acts as a competitive inhibitor of α-ketoglutarate resulting in inhibition of multiple αKG-dependent dioxygenases including TET2. In addition, IDH1/IDH2 mutations are associated with global cytosine hypermethylation signatures that lead to impaired haematopoietic differentiation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Common recurrent IDH mutations are located in codon 132 in exon 4 of the IDH1 gene and in codon 140 and codon 172 in exon 4 of the IDH2 gene. IDH1 encodes an enzyme that localizes to the cytosol and peroxisomes, while IDH2 encodes an enzyme that localizes to the mitochondria [7].…”
Section: Introductionmentioning
confidence: 99%